The sermons of Jonathan Edwards : a reader - Edwards, Jonathan, 1703-1758 (Yale University Press, 1999)
Jonathan Edwards, widely considered America's most important Christian thinker, was first and foremost a preacher and pastor who guided souls and interpreted religious experiences. His primary tool in achieving these goals was the sermon, out of which grew many of his famous treatises. This selection of Edwards' sermons recognizes their crucial role in his life and art. The fifteen sermons, four of which have never been published before, reflect a life dedicated to experiencing and understanding spiritual truth. Chosen to represent a typical cycle of Edwards' preaching, the sermons address a wide range of occasions, situations, and states, corporate as well as personal. The book also contains an introduction that discusses Edwards' contribution to the sermon as a literary form, places his sermons within their social and cultural contexts, and considers his theological aims as a way of familiarizing the reader with the "order of salvation" as Edwards conceived of it. Together, the sermons and the editors' introduction offer a rounded picture of Edwards the preacher, the sermon writer, and the pastoral theologian.